Implementasi Program Keagamaan sebagai Upaya Meningkatkan Jiwa Religius Siswa MTsN 4 Mandailing Natal - Suryadi Nasution; Muhammad Rifai Sirefar; Putriana Nasution; Putri Amanda; Fitri Padilah; Eka Wanda Rangkuti; Iqlimah Batubara; Nurul Sakinah Pane; Riski Salamah; Nabilah Lubis; Nur Azizah Nasution (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2025)
Wirid Yasin is one of the practices that are widely carried out by Muslims to get closer to Allah SWT and improve the spiritual aspects in everyday life. This study uses a qualitative approach with a case study method, which involves observation, interviews, and documentation to collect data related to the implementation of wirid Yasin in the school. The results of the study indicate that the routine implementation of wirid Yasin at MTsN 4 Mandailing Natal has a positive impact on improving the quality of students' religious life. Students experience improvements in spiritual aspects, such as increased piety, inner peace, and better understanding of religion. In addition, wirid Yasin also contributes to creating a religious atmosphere in the school environment, which in turn affects students' morality and attitudes in everyday life. Therefore, the implementation of wirid Yasin can be an effective effort to improve the quality of students' religious life at MTsN 4 Mandailing Natal.